Morphological, Chemical and Mineralogical Properties of the Soils of Abugi, Nigeria, and their Agricultural Potential - K. A., Adegbite; J. A., Ogunwale (Universiti Putra Malaysia Press, 1994)
Three soil profiles at Abugi in the flood plains of River Niger, Kogi State, Nigeria were studied. The soils are moderately acidic (PH 4.7 to 6.0) in the suiface horizons. Exchangeable cations are low with the exception of calcium which is moderate and is the dominant exchangeable cation with values ranging from 0.50 to 7.00 cmol(+)/kg of soil. The dominant clay minerals are kaolinite, degraded-mica and quartz, while traces of smectite and feldspar were also detected. Abugi profile one was classified as Eutric Planosol (FAD 1988) or Fluvaquentic Humaquept (Soil Survey Staff 1992) while profiles two and three were both classifzed as Eutric Gleysol (FAD 1988) or Aeric Tropaquept (Soil Survey Staff 1992). The soils of Abugi area offer great potential for rice and sugarcane production if excessive flooding and increasing acidity can be controlled.